Two Decades of Palm Oil Research: A Global Bibliometric Analysis - Judijanto, Loso (West Science Interdisciplinary Studies, 2025)
Over the past two decades, palm oil has emerged as one of the most widely studied commodities due to its central role in global food, energy, and sustainability debates. This study conducts a comprehensive bibliometric analysis of palm oil research published between 2005 and 2025, drawing on data retrieved from the Scopus database. Using tools such as VOSviewer and Excel, the study maps publication trends, influential authors, leading journals, thematic clusters, and patterns of international collaboration. The results reveal that early research was dominated by studies on biodiesel production and chemical conversion processes, while more recent years have seen a shift toward sustainability, environmental management, and waste valorization. Malaysia and Indonesia emerge as the two central hubs of research output and collaboration, reflecting their positions as global leaders in palm oil production. Influential journals, particularly the Journal of the American Oil Chemists’ Society (JAOCS) and the Journal of Oil Palm Research, serve as intellectual anchors in the field. The co-occurrence and density visualizations highlight the expansion of palm oil studies from engineering and agronomic concerns to broader interdisciplinary discourses linking agriculture, energy, and global development. This study contributes to the literature by offering both theoretical insights into the intellectual structure of palm oil research and practical implications for policymakers, industry stakeholders, and scholars seeking to align future research with sustainability and international collaboration agendas.